The National Kidney Foundation Guideline on Estimation of the Glomerular Filtration Rate - Jones, Graham RD (The Australian Association of Clinical Biochemists, 2003)
The Kidney Disease Outcomes Quality Initiative (K/DOQI) is a set of evidence-based clinical practice guidelines from the National Kidney Foundation in the USA. All K/DOQI guidelines are published in the American Journal of Kidney Diseases and can also be accessed without restriction on the internet at: http://www.kdoqi.org. Our aim in this article is to critically review one section of the recently released guideline "K/DOQI Clinical Practice Guidelines for Chronic Kidney Disease: Evaluation, Classification, and Stratification". Part 5 of this document, "Evaluation of laboratory measurements for clinical assessment of kidney disease" includes Guideline 4: "Estimation of GFR".1 The summary section of the guideline is reproduced in the box and is presented in the original with 16 pages of explanation and supporting material. In this review we will critically assess the various components of this guideline under headings based on the statements in the summary.